Islamic Education Model - Abdul Wahab Syakhrani (Indonesian Journal of Education (INJOE), 2021)
The model of education in Islam cannot be separated from the role of a leader, in which the leader is able to provide a model of education that occurs in institutions, both in households, schools and communities.